Implementation of Financial Accounting Standards for Micro, Small and Medium Entities (Sak - Emkm) at MSME Photocopy Boom Karawang - Hoerunisa, Tiva; Lasmini, Lilis; Arimurti, Trias (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
This research was conducted with the aim of knowing the preparation of financial statements because so far Photocopy of Boom Karawang has not prepared financial statements in accordance with the Financial Accounting Standards of Micro, Small and Medium Entities (SAK EMKM). The type of research used is a type of qualitative descriptive research. The results of research from interviews with MSME owners Photocopy of Boom Karawang have so far not prepared financial statements, this is due to the preparation of financial reports based on SAK EMKM has a process that requires time, energy and limited knowledge possessed by MSME actors based on financial data obtained, The preparation of financial statements prepared by MSMEs Photocopy of Boom Karawang is only a simple recording containing income and expenses recorded in an ordinary record.